Corporative Indian‪ Knowledge System - Gopal kumawat, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The Indian Knowledge System (IKS) is a collection of knowledge, beliefs, and practices that has developed over thousands of years in India. It includes a wide range of disciplines, such as: mathematics, astronomy, medicine, philosophy, ecology, architecture, arts, languages, and literature. This knowledge system encompasses a wide range of subjects including philosophy, religion, science, mathematics, medicine, astrology, and literature. It is based on a holistic approach that integrates different aspects of human life, such as mind, body, and spirit. One of the key characteristics of the Indian Knowledge System is its emphasis on the interconnectedness and interdependence of all beings and the universe. The study attempts to determine the potential of India’s ancient knowledge system in providing solutions to the organization’s management This study mainly discusses corporate lessons from Bhagawad Gita, Ramayan and Mahabharat. The study was based on secondary data. The study concluded that corporate teachings that are provided by Bhagawad Gita, Ramayan, and Mahabharat are very useful for corporate people as it provides them an aid in increasing their competency, skills and helps them in facing their fear of failure.
Keywords: Indian knowledge system; IKS; Upanishads; Vedas; Ayurveda; Yoga; Vedic astrology; traditional; corporate; lessons